EVALUATION OF THE APPLICATION OF BIOSECURITY AFTER THE AFRICAN SWINE FEVER EPIDEMIC ON PIG FARMING IN KUPANG REGENCY, EAST NUSA TENGGARA - Kurniawati, Galih Shinta; Detha, Annytha Ina Rohi; Kallau, Novalino Harold Geoffrey (Buletin Veteriner Udayana, 2023)
African swine fever (ASF) is an infectious and hemorrhagic disease that attacks pigs caused by a double-stranded DNA virus, in family Asfarviridae and genus Asfivirus. Known that vaccines and treatments for pigs infected by the virus have not been found can increase the risk of transmission in pig farms, so that biosecurity is a very important measure in reducing or minimizing the spread and prevention of the disease. The purpose of this study is to identify the types and evaluation of biosecurity application techniques on pig farms after ASF outbreak in Kupang Regency. Method of this study is used cross sectional method and descriptive analysis by conducting observational interview and data collections by filling the questionnaires. Data of this study are presented in the form of a weight processing table and a comparison table of types of biosecurity. There are three types of biosecurity, conceptual, structural and operational biosecurity. Value of the application of biosecurity of the three types of biosecurity in six farms got a good category, namely conceptual biosecurity has value of 128, structural biosecurity has value of 261, and operational biosecurity has value of 204. Evaluation the values of the three types of biosecurity in 6 pig farms has good category. This category is evidenced by the application of the three types of biosecurity by the six pig farms. Researchers suggest to increasing the application of biosecurity, especially manage the distances from residential areas by means of higher walls, making septic tanks for waste collection so that they are not environmentally friendly, providing sanitation and disinfection facilities, namely places and soap for washing hands and feet, toilet facilities, and procurement of PPE for workers.